Help-Seeking While Problem Solving Adult Care-Givers and the Zone of Proximal Development - Zack, Vicki ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1995)
This investigation is part of an ongoing, larger study which is looking at joint activity and appropriation of new understandings in an inquiry mathematics classroom setting. Instances of help-seeking which occurred while children were endeavoring to solve non-routine problems at home were analyzed. Considered in this study were (1) the kind of help sought by the child, (2) the kind of help offered by the adult, (3) how extensive the help was, and (4) the sense the child made of the help. The data sources included the children's writing in their math logs, and their explanatory presentations subsequently given to peers in class. Findings suggest that (1) the children sought and received help predominantly with respect to problem-solving strategies and mathematical concepts, (2) interactions with adults were evenly distributed among all the students-the adept, moderately adept, and less adept-in that some did ask for help while others rarely or never did, and (3) the less adept children were less specific in describing the kind of help sought/received while the more adept children's' requests were more specific and focused. (Author)
Sponsoring Agency: Social Sciences and Humanities Research Council of Canada, Ottawa (Ontario).
Contract Number: 410-94-1627.
ERIC Note: Paper presented at the Annual Meeting of the North American Chapter of the International Group for the Psychology of Mathematics Education (17th, Columbus, OH, October 21-24, 1995). For entire conference proceedings, see SE 057 177.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cognitive Processes; Elementary School Students; Grade 5.; Help Seeking; Intermediate Grades; Mathematics Instruction; Parent Participation; Problem Solving; Student Journals; Zone of Proximal Development; Reports, Research; Speeches/Meeting Papers